Immediate loading of single implants in the posterior region: a literature review - Do, Thanh Tin; Vo, Hoang Thuy Tien; Nguyen, Thi Thuy Duong; Trần, Tấn Tài (Tạp chí Y Dược Huế, 2026)
ABSTRACT This review evaluates the clinical considerations of immediate loading protocols for single dental implants in the posterior region. Immediate loading offers advantages such as reduced treatment time and improved patient comfort but requires strict criteria to ensure success. Primary implant stability—measured via insertion torque and resonance frequency analysis—is the most critical factor, with values of ≥30–45 Ncm and ISQ ≥60 often cited as thresholds. Bone characteristics varies in significantly affects outcomes, with the posterior mandible typically providing better support due to higher density and thicker cortical bone layer. Guided surgical techniques enhance placement accuracy and reduce complications compared to freehand methods. Despite generally high success rates, both mechanical and biological complications still remain concerns. Overall, with careful case selection and appropriate technique, immediate loading is a reliable and predictable option for single posterior implants.